Deskripsi Gejala dan Tingkat Serangan Penyakit Busuk Kuning Pada Batang Tanaman Buah Naga Merah (Hylocereus polyrhizus, L.) di Padang Pariaman, Sumatera Barat - Dina Barthana; Nasril Nasir; - Jumjunidang (Universitas Andalas, 2013)
The study about on the description of symptoms and disease severity of yellow disease stem rot of red dragon fruit (Hylocereus polyrhizus, L) in Padang Pariaman, West Sumatera has been was studied from December 2012 to February 2013. The study was conducted at the Laboratory of plant diseases and the screen house of Indonesian Tropical Fruit Research Institute Solok and Microbiology laboratory of Biology Department of Mathematic and Natural Science, Andalas University, Padang. The purpose of the study was to characterize and identify the symptoms of the yellow disease stem rot on dragon fruit. This study was used direct observation method and the data were analyzed descriptively. The result showed that percentage of yellow disease stem rot of dragon fruit in Padang Pariaman was 99,5% while disease severity index was 2,59 (moderate severity). The microbes found at the time of isolation were Fusarium sp., Pestalotiopsis sp., Colletotrichum gloeosporioides, Sclerotium sp., fungi (sp.1) and bacteria (sp. 1). The microbes that caused yellow disease stem rot of red dragon fruit which was investigated by using postulate Koch test was Fusarium sp.Key words: Symptoms, disease severity, yellow disease stem rot, identification